ORAL REHABILITATION OF THE CHANGES IN THE ELEMENTS OF THE ORAL CAVITY IN PATHOLOGICAL PREGNANCY - Alina Calin; Mohammad Shalalfeh; Corina Cecilia Manole Palivan; Gabi Topor; Radu Doliscinschi; Iolanda Florentina Dumitru; Ionuta Grigore; Ovidiu Schipor; Kamel Earar (Romanian Society of Oral Rehabilitation, 2020)
Dentistry as a branch of medical science is no exception to the overall evolution of human knowledge, in a field of collective interest that embodies strong research forces. For dental pathology, as well as for other medical fields, the pathological anatomy proves to be indispensable for the correct, scientific diagnosis and treatment and for the formation of medical thinking. Having in mind the great diversity of th oral pathology, the necessity of anatomo-pathological investigation is confirmed by its possibilities to elucidate the structural, material foundation of the quasi-totality of the diseases in this field and to differentiate them on this basis, offering for the clinic a conclusive diagnosis. Oral rehabilitation consists in diagnosing and treating the entire pathology in the oral cavity, in the joint, muscle, bone, by correcting changes due to tooth loss, abrasions, dental malpositions or the removal of tumors from the face. Pregnancy is a particular physiological condition characterized by numerous hormonal and metabolic changes with a transient character, but in some cases can become pathological aspects.Clinical notices in medical practice, as well as some research has brought into attention the importance of normal oro-dental physiology as well as the integrity of the dento-maxillary apparatus during pregnancy. By their high frequency and severity of clinical form, oro-dental diseases have become one of the basic problems of public health protection.